2019
DOI: 10.5339/qmj.2019.9
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and reporting confidence analysis of sequential dual-energy subtraction for thoracic x-ray examinations

Abstract: Rationale and objectives: We aimed to report and compare accuracy, reproducibility, and reporting confidence between thoracic dual-energy subtraction (DES) and routine posterior–anterior chest radiography (PA-CR) techniques. Materials (patients) and methods: We obtained DES (D1–D4) images from 96 patients using DES and a high-resolution dynamic flat-panel detector in combination. We compared the DES images of these patients with their PA-CR images. The maximum time interval between performing DES and PA-CR was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Nevertheless, most previous studies have evaluated the detectability of the lung nodules rather than the presence or absence of nodule calcification 2 , 3 , 5 – 10 . In addition, most previous studies used dual-shot DES 3 , 6 , 9 , 10 or used one-shot DES with film-screen radiography or computed radiography 4 , 5 , 8 , 11 ; these studies did not use one-shot DES with a flat-panel detector. To the best of our knowledge, the present study is the first to evaluate the effectiveness of one-shot DES with a flat-panel detector to differentiate between calcified and non-calcified nodules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, most previous studies have evaluated the detectability of the lung nodules rather than the presence or absence of nodule calcification 2 , 3 , 5 – 10 . In addition, most previous studies used dual-shot DES 3 , 6 , 9 , 10 or used one-shot DES with film-screen radiography or computed radiography 4 , 5 , 8 , 11 ; these studies did not use one-shot DES with a flat-panel detector. To the best of our knowledge, the present study is the first to evaluate the effectiveness of one-shot DES with a flat-panel detector to differentiate between calcified and non-calcified nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Although the usefulness of DES has already been reported on chest radiography, most studies have not evaluated distinguishability between calcified and non-calcified nodules, but rather evaluated nodule detectability 2 , 3 , 5 – 10 . In addition, most studies have used two-shot DES 3 , 6 , 9 , 10 or have used one-shot DES by means of film-screen radiography or computed radiography instead of flat-panel detectors 4 , 5 , 8 , 11 . Therefore, the diagnostic performance of one-shot DES with a flat-panel detector for calcified nodules is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…DE is a new imaging modality with the potential to overcome these difficulties. In DE, a post-processing algorithm separates calcium-containing structures from soft-tissue components and overcomes the problem of superimposition of several structures [34].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies could show that DE improves the sensitivity for shading lesions, such as the detection of infectious consolidations, tumors, interstitial lung changes, and aortic or tracheal calcification compared to CR images [18][19][20][21]. Other studies have shown that DE can reduce diagnostic errors of chest pathologies and prevent misdiagnosis of consolidations or lung nodules, for example, also by less-experienced radiologists [34,36]. The higher accuracy for detecting focal opacities (i.e., lung nodules or infectious infiltrates) was attributed to the better accentuation of lung abnormalities [37].…”
Section: Discussionmentioning
confidence: 99%
“…По данным ряда работ эффективность ДЭР в диагностике различных заболеваний легких превосходит стандартную цифровую рентгенографию (ЦР) при сопоставимой дозовой нагрузке, тем не менее двухэнергетическая методика пока не нашла свое место в алгоритме лучевого обследования органов грудной клетки [3][4][5].…”
unclassified